Method for preparing alanine by photoreforming polylactic acid plastic

By using cobalt phosphide/cadmium sulfide photocatalyst in ammonia water for photocatalytic reaction, the waste polylactic acid plastic is converted into alanine, which solves the problems of high energy consumption and low selectivity in the existing technology, and achieves an efficient and economical upgrade process.

CN120208800APending Publication Date: 2025-06-27TECHNICAL INST OF PHYSICS & CHEMISTRY - CHINESE ACAD OF SCI

Patent Information

Application Number
CN202311797575.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-25
Publication Date
2025-06-27

AI Technical Summary

Technical Problem

In the prior art, when upgrading waste polylactic acid plastics into valuable chemicals, there are high energy consumption, low product selectivity and complex product separation/purification processes, and the degradation process is controlled by the thermodynamic limits, resulting in waste of chemical resources.

Method used

The polylactic acid plastic is photocatalyzed in ammonia water by using cobalt phosphide/cadmium sulfide photocatalyst to produce alanine. The reaction conditions are mild and the process is simple.

Benefits of technology

It achieves high alanine yield and selectivity, mild reaction conditions, simple process, and has high economic value and application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004628118160000011
    Figure HDA0004628118160000011
  • Figure HDA0004628118160000012
    Figure HDA0004628118160000012
  • Figure HDA0004628118160000021
    Figure HDA0004628118160000021
Patent Text Reader

Abstract

The invention discloses a method for preparing alanine by photoreforming polylactic acid plastic, which is characterized by comprising the following steps: placing polylactic acid plastic and a photocatalyst in ammonia water to obtain a reaction solution, and adding the reaction solution into a light-transmitting reactor; and in an inert atmosphere, irradiating the reaction liquid with a light source at 60-80 DEG C for 5-20 hours, and carrying out a photocatalytic reaction to obtain the alanine. According to the method, the process of catalyzing the polylactic acid plastic to be converted into the alanine is achieved through the one-step method with the self-made cobalt phosphide / cadmium sulfide as the photocatalyst, high selectivity and stability are achieved, meanwhile, the method is simple in process, raw materials are easy to obtain, reaction conditions are mild, separation and purification operation is easy, and high economic value and application value are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the fields of photocatalysis and waste plastic reforming. The more specific steps are as follows: It relates to a method for preparing alanine by photoreforming polylactic acid plastics. Background Art

[0002] As a biodegradable plastic, polylactic acid plastic can be degraded by microorganisms in nature into small molecules (such as water, carbon dioxide and methane), avoiding the problem of "white pollution", so it has received extensive attention. However, the spontaneous degradation process of waste polylactic acid plastic is very slow and depends to a large extent on environmental conditions. In addition, even if it finally decomposes, the products are carbon dioxide and water, which not only exacerbates the global greenhouse effect but also causes a huge waste of carbon resources. Therefore, compared with natural degradation, there is an urgent need to develop a sustainable strategy to upgrade waste polylactic acid plastic into valuable chemicals with high activity and high selectivity.

[0003] Currently, the recycling of waste polylactic acid plastic mainly relies on chemical recycling. For example, hydrolysis is the most commonly used method, which can recycle polylactic acid into oligomers or lactic acid. However, this method not only consumes a large amount of corrosive strong acids or strong bases but also requires a certain temperature (120 - 350 °C) and pressure (∼10 MPa), causing environmental and operation problems and posing challenges to practical applications. In addition, some alternative methods (such as alcoholysis, ammonolysis) have also been used to convert polylactic acid into lactate or alanine. However, these methods have an inherent drawback: the degradation process is controlled by the thermodynamic limit and requires an excessive amount of reagents to increase the degradation yield, thus inevitably causing a waste of chemical resources. Patent CN115073416A discloses a method for catalytic thermal decomposition of polylactic acid, in which polylactic acid is thermally decomposed under relatively mild conditions by a superbase catalyst. However, the pyrolysis method requires high temperature and high pressure, resulting in high energy consumption, low product selectivity and a complex product separation / purification process, limiting its applicability.

[0004] Photoreforming technology uses inexhaustible clean solar energy to produce redox substances or reaction intermediates, and realizes the decomposition and upgrading of plastics at ambient temperature and pressure, which has received extensive attention in recent years. Currently, various photoreactions and photocatalysts have been developed for photocatalytic plastic recycling coupled with hydrogen production. However, it is still in the early stage of development and has the following problems: 1) Waste polylactic acid plastic requires pretreatment with strong acids or strong bases; 2) Poor catalytic efficiency and low product selectivity lead to complex product separation / purification procedures, thus inevitably increasing costs. Summary of the Invention

[0005] To solve the above problems, the object of the present invention is to provide a method for preparing alanine by photoreforming polylactic acid plastic. This method converts polylactic acid plastic into alanine under the action of cobalt phosphide / cadmium sulfide photocatalyst, with a high alanine yield and selectivity, and the reaction conditions are mild and the process is simple, having high economic value and application value.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] The present invention discloses a method for preparing alanine by photoreforming polylactic acid plastic, comprising the following steps:

[0008] Put polylactic acid plastic (PLA) and photocatalyst into ammonia water to obtain a reaction solution, and add the reaction solution into a light-transmitting reactor;

[0009] Under an inert atmosphere, irradiate the reaction solution with a light source, and carry out a photocatalytic reaction at 60 - 80 °C for 5 - 20 h to obtain alanine;

[0010] Among them, the photocatalyst is selected from cobalt phosphide / cadmium sulfide (CoP / CdS).

[0011] In the present invention, when irradiated with visible light, the cobalt phosphide / cadmium sulfide photocatalyst will generate photogenerated electrons and holes. The photogenerated electrons accelerate proton reduction, and the holes dominate the oxidation of polylactic acid, thereby jointly producing alanine. The specific reaction process is as follows: First, PLA is partially ammonolyzed to ammonium lactate. Subsequently, the photogenerated holes on the valence band of CdS rapidly oxidize ammonium lactate to produce pyruvic acid, which then reacts with ammonia to form an imine intermediate. Correspondingly, CoP in-situ grown on CdS can rapidly extract photogenerated electrons from CdS to accelerate the reduction of protons to ·H active species. Finally, the imine intermediate reacts with the ·H active species to form alanine. As ammonium lactate is consumed, the equilibrium of the ammonolysis reaction is disrupted, and ammonolysis will continue to occur until PLA is completely consumed.

[0012] Further, the mass ratio of the polylactic acid plastic to the photocatalyst is 5 - 20:1; exemplarily, it can be 5:1, 10:1, 15:1, or 20:1, etc.

[0013] Further, the cobalt phosphide is loaded on the surface of cadmium sulfide nanorods as a cocatalyst, and the mass ratio of the cobalt phosphide to the cadmium sulfide is 1:13 - 33; exemplarily, the mass ratio of the cobalt phosphide to the cadmium sulfide can be 1:13, 1:15, 1:18, 1:20, 1:25, 1:30, or 1:33, etc.

[0014] Further, the photocatalyst is prepared according to the following steps:

[0015] The preparation of cadmium sulfide was carried out by the classical solvothermal method. Cadmium salt and thiourea were successively dissolved in ethylenediamine. After stirring for 20 - 30 min, it was transferred into a stainless - steel autoclave with a polytetrafluoroethylene liner and heated at 150 - 160 °C for 24 - 48 hours to obtain cadmium sulfide nanorods;

[0016] The cadmium sulfide nanorods were added to a mixed solution of ethanol and water. Cobalt salt and ammonia water were added thereto. It was heated at 70 - 90 °C for 20 - 25 hours, and then transferred into a stainless - steel autoclave with a polytetrafluoroethylene liner and heated at 140 - 160 °C for 3 - 5 hours to obtain cobalt tetroxide / cadmium sulfide;

[0017] The cobalt tetroxide / cadmium sulfide and sodium hypophosphite were mixed and ground, and then transferred to a tubular furnace and calcined under an inert atmosphere to obtain cobalt phosphide / cadmium sulfide.

[0018] Furthermore, the cadmium salt is selected from cadmium nitrate tetrahydrate; the molar ratio of the cadmium salt to thiourea is 1:2 - 3.

[0019] Furthermore, the concentration of the cadmium salt in ethylenediamine is 0.2 - 0.5 mol / L; preferably 0.3 mol / L.

[0020] Furthermore, the cobalt salt is selected from cobalt acetate tetrahydrate and / or cobalt nitrate hexahydrate; the mass ratio of the cadmium sulfide nanorods to the cobalt salt is 5 - 7:1.

[0021] Furthermore, the calcination conditions are as follows: heating at a heating rate of 2 - 3 °C·min -1 to 300 - 350 °C and holding for 3 - 5 h.

[0022] Furthermore, the light source is selected from one of sunlight, xenon lamp, mercury lamp, and LED lamp.

[0023] Furthermore, after the photocatalytic reaction is completed, it also includes separating and purifying the product.

[0024] Furthermore, the steps of the separation and purification are as follows:

[0025] The reaction solution after illumination was centrifuged and filtered through a polyethersulfone membrane. After decolorization, rotary evaporation, and recrystallization, alanine crystals were obtained.

[0026] The beneficial effects of the present invention are as follows:

[0027] The present invention discloses a method for preparing alanine from photo-reforming polylactic acid plastics. In the present invention, a cobalt phosphide / cadmium sulfide catalyst for photocatalytic reaction was first prepared, and then a series of reactions of polylactic acid plastics were induced by cobalt phosphide / cadmium sulfide under visible light irradiation, and finally converted into the target product alanine, showing high selectivity and stability. Within the first 5 h, the production rate of alanine can reach 2.4 mmol g cat -1 h -1 , and the selectivity remains greater than 75% after 20 h of light irradiation. At the same time, this method has a simple process, easily available raw materials, mild reaction conditions, simple separation and purification operations, and has high economic value and application value.

[0028] The present invention also extends the reaction raw materials to some waste polylactic acid plastic products, and finds that the reaction system of the present invention can also have high conversion performance, so it has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The following further details the specific embodiments of the present invention with reference to the accompanying drawings.

[0030] Figure 1 Shows the Raman spectrum of the cobalt phosphide / cadmium sulfide photocatalyst prepared in Example 1.

[0031] Figure 2 Shows the XRD spectrum of the cobalt phosphide / cadmium sulfide photocatalyst prepared in Example 1.

[0032] Figure 3 Shows the EDS energy spectrum of the cobalt phosphide / cadmium sulfide photocatalyst prepared in Example 1.

[0033] Figure 4 Shows the comparison of the total products generated in the photocatalytic reaction of Example 2 with the 1 1H NMR spectrum of the alanine standard. DETAILED DESCRIPTION OF THE EMBODIMENTS

[0034] To more clearly illustrate the present invention, the present invention will be further described below with reference to preferred embodiments and the accompanying drawings. Similar components in the drawings are denoted by the same reference numerals. Those skilled in the art should understand that the content specifically described below is illustrative rather than restrictive, and should not be used to limit the protection scope of the present invention.

[0035] Example 1: Preparation of cobalt phosphide / cadmium sulfide

[0036] 1) Cadmium sulfide nanorods were prepared by a hydrothermal method. The specific steps were as follows: Cadmium nitrate tetrahydrate (15 mmol) and thiourea (45 mmol) were successively dissolved in 50 mL of ethylenediamine. After stirring for 30 minutes, it was transferred to a stainless-steel autoclave with a polytetrafluoroethylene liner and heated at 160 °C for 48 hours. After natural cooling, the yellow precipitate of cadmium sulfide was collected by centrifugation, washed several times with deionized water and ethanol, and then dried in a vacuum oven.

[0037] 2) 600 mg of the prepared cadmium sulfide nanorods were added to a 250 mL eggplant-shaped flask. Then, 24 mL of ethanol and 0.5 mL of deionized water were added and stirred for 20 min. After ultrasonic treatment at room temperature for 30 min, 0.6 mL of 0.5 M cobalt acetate tetrahydrate was added dropwise thereto, and then 0.5 mL of ammonia water was added dropwise. The mixture was stirred for 30 min, 95 mL of ethanol was added, and it was heated at 80 °C for 22 hours to obtain a suspension. Subsequently, the suspension was transferred to a stainless-steel autoclave with a polytetrafluoroethylene liner and heated at 150 °C for 4 hours. After natural cooling, the brown product cobalt tetroxide / cadmium sulfide was collected by centrifugation.

[0038] 3) 120 mg of cobalt tetroxide / cadmium sulfide and 280 mg of sodium hypophosphite solid were mixed and ground, and then transferred to a quartz boat in a tubular furnace. Under a flowing Ar atmosphere, the sample was heated to 300 °C at a heating rate of 2 °C·min -1 and held for 4 hours. Finally, the obtained solid was cooled to room temperature, washed three times with water and ethanol, and dried in a vacuum oven to obtain a composite material cobalt phosphide / cadmium sulfide, and the mass ratio of cobalt phosphide to cadmium sulfide was 1:20.

[0039] Figure 1 The Raman spectrum of the cobalt phosphide / cadmium sulfide photocatalyst prepared in Example 1 is shown, indicating the successful preparation of cadmium sulfide. Since the content of cobalt phosphide in the composite material is low, the peaks of cobalt phosphide can hardly be seen, and it is also found that there is a shift for CoP / CdS compared with CdS, representing an electron interaction after CoP loading.

[0040] Figure 2 The XRD spectrum of the cobalt phosphide / cadmium sulfide photocatalyst prepared in Example 1 is shown, indicating that the prepared cadmium sulfide has a hexagonal phase structure.

[0041] Figure 3 The EDS energy spectrum shows that the prepared composite material mainly contains four elements: cadmium, sulfur, cobalt, and phosphorus.

[0042] Example 2: Photocatalytic synthesis of alanine from polylactic acid plastic

[0043] The photocatalytic reaction was carried out in a reactor under a 300 W xenon lamp. The lighting device includes: a quartz window, a thermocouple, a pressure gauge, and an air inlet. The specific steps are as follows:

[0044] Disperse 10 mg of the cobalt phosphide / cadmium sulfide catalyst prepared in Example 1 in 10 mL of ammonia water containing 100 mg of polylactic acid plastic to obtain a reaction solution, and add the reaction solution to a light-transmitting reactor. Then, purge the reactor with nitrogen for 30 minutes to remove dissolved oxygen. Under 1 bar of nitrogen, irradiate the reaction solution with a 300 W xenon lamp while controlling the reaction solution at 80 °C.

[0045] Table 1 records the change in the amount of product generated over time. It can be seen that within the first 5 h, the production rate of alanine reaches 2.4 mmol g cat -1 h -1 and still maintains a relatively high production rate after 20 h of illumination. The production rate of alanine reaches 0.88 mmol g within 15 - 20 h cat -1 h -1 .

[0046] Table 1

[0047] Reaction time 5h 10h 15h 20h Alanine production <![CDATA[12mmol g Cat -1 > <![CDATA[20mmol g Cat -1 > <![CDATA[31.6 mmol g Cat -1 > <![CDATA[36mmol g Cat -1 >

[0048] Figure 4 is the 1H NMR spectrum of the total product after the photoreaction (reaction for 60 h). It can be seen from the figure that after the photoreaction is completed, polylactic acid is basically completely converted, the conversion rate of polylactic acid is 100%, and the selectivity of alanine is greater than 75%. 1

[0049] Example 3: Separation and purification of alanine product

[0050] Centrifuge the reaction solution after 20 h of illumination in Example 2 and filter it twice through a polyethersulfone membrane (0.22 μm), perform decolorization treatment with activated carbon, then rotary evaporate at 55 °C to remove ammonia and concentrate. Finally, add an excess of methanol for recrystallization treatment, filter, wash, and dry the filter residue to obtain alanine crystals.

[0051] Example 4: Stability test

[0052] Perform a stability test on the cobalt phosphide / cadmium sulfide prepared in Example 1. The test is as follows:

[0053] The photocatalytic reaction was repeated 4 times using the repeatedly phosphated cobalt / sulfide cadmium according to the photocatalytic step of Example 2, with each reaction time being 5 h. The production rate of alanine at the end of each reaction was recorded. Cadmium sulfide was used as a control group for comparison (the amount of cadmium sulfide used was 10 mg). The results are shown in Table 2. It can be seen that the cobalt / sulfide cadmium still maintained 73% of its initial activity after four cyclic experiments, indicating that the catalyst has good stability.

[0054] Table 2

[0055] Number of cycles Once Twice Thrice Four times Cobalt phosphide / cadmium sulfide <![CDATA[2.4 mmol g cat -1 h -1 > <![CDATA[2.08 mmol g cat -1 h -1 > <![CDATA[1.84 mmol g cat -1 h -1 > <![CDATA[1.76 mmol g cat -1 h -1 > Cadmium sulfide <![CDATA[0.56 mmol g cat -1 h -1 > <![CDATA[0.4 mmol g cat -1 h -1 > <![CDATA[0.32 mmol g cat -1 h -1 > <![CDATA[0.24 mmol g cat -1 h -1 >

[0056] Example 5

[0057] 5 mg of the cobalt / sulfide cadmium catalyst prepared in Example 1 was dispersed in 10 mL of ammonia water containing 100 mg of polylactic acid plastic to obtain a reaction solution, and the reaction solution was added to a light-transmitting reactor. Then, the reactor was purged with nitrogen for 30 minutes to remove dissolved oxygen. Under 1 bar of nitrogen, the reaction solution was irradiated with a 300 W xenon lamp, and the reaction solution was controlled to react at 80 °C.

[0058] After testing, within the initial 5 h, the production rate of alanine reached 1.76 mmol g cat -1 h -1 。

[0059] Example 6

[0060] 20 mg of the cobalt / sulfide cadmium catalyst prepared in Example 1 was dispersed in 10 mL of ammonia water containing 100 mg of polylactic acid plastic to obtain a reaction solution, and the reaction solution was added to a light-transmitting reactor. Then, the reactor was purged with nitrogen for 30 minutes to remove dissolved oxygen. Under 1 bar of nitrogen, the reaction solution was irradiated with a 300 W xenon lamp, and the reaction solution was controlled to react at 80 °C.

[0061] After testing, within the initial 5 h, the production rate of alanine reached 1.2 mmol g cat -1 h -1 。

[0062] Based on the experimental results of Example 2 and Examples 5 - 6, it was found that when the polylactic acid plastic and the photocatalyst were subjected to photocatalytic reaction under different dosage ratio relationships, the best reaction activity was exhibited when the mass ratio of the polylactic acid plastic to the photocatalyst was 10:1.

[0063] Example 7

[0064] Referring to the preparation process of cobalt phosphide / cadmium sulfide in Example 1, adjust the addition amount of cobalt acetate hydrate in Step 2, and finally obtain a cobalt phosphide / cadmium sulfide catalyst with a mass ratio of cobalt phosphide to cadmium sulfide of 1:100, and then carry out the photocatalytic reaction.

[0065] Disperse 10 mg of the above-prepared cobalt phosphide / cadmium sulfide catalyst in 10 mL of ammonia water containing 100 mg of polylactic acid plastic to obtain a reaction solution, and add the reaction solution into a light-transmitting reactor. Then, purge the reactor with nitrogen for 30 minutes to remove the dissolved oxygen. Under 1 bar of nitrogen, irradiate the reaction solution with a 300 W xenon lamp, and at the same time control the reaction solution at 80 °C for reaction. After testing, within the initial 5 h, the production rate of alanine reaches 0.77 mmol g cat -1 h -1 。

[0066] Example 8

[0067] Referring to the preparation process of cobalt phosphide / cadmium sulfide in Example 1, adjust the addition amount of cobalt acetate hydrate in Step 2, and finally obtain a cobalt phosphide / cadmium sulfide catalyst with a mass ratio of cobalt phosphide to cadmium sulfide of 3:100, and then carry out the photocatalytic reaction.

[0068] Disperse 10 mg of the above-prepared cobalt phosphide / cadmium sulfide catalyst in 10 mL of ammonia water containing 100 mg of polylactic acid plastic to obtain a reaction solution, and add the reaction solution into a light-transmitting reactor. Then, purge the reactor with nitrogen for 30 minutes to remove the dissolved oxygen. Under 1 bar of nitrogen, irradiate the reaction solution with a 300 W xenon lamp, and at the same time control the reaction solution at 80 °C for reaction. After testing, within the initial 5 h, the production rate of alanine reaches 1.38 mmol g cat -1 h -1 。

[0069] Example 9

[0070] Referring to the preparation process of cobalt phosphide / cadmium sulfide in Example 1, adjust the addition amount of cobalt acetate hydrate in Step 2, and finally obtain a cobalt phosphide / cadmium sulfide catalyst with a mass ratio of cobalt phosphide to cadmium sulfide of 7.5:100, and then carry out the photocatalytic reaction.

[0071] Disperse 10 mg of the above-prepared cobalt phosphide / cadmium sulfide catalyst in 10 mL of ammonia water containing 100 mg of polylactic acid plastic to obtain a reaction solution, and add the reaction solution into a light-transmitting reactor. Then, purge the reactor with nitrogen for 30 minutes to remove the dissolved oxygen. Under 1 bar of nitrogen, irradiate the reaction solution with a 300 W xenon lamp, and at the same time control the reaction solution at 80 °C for reaction. After testing, within the initial 5 h, the production rate of alanine reaches 2.16 mmol g cat-1 h -1 。

[0072] By synthesizing the experimental results of Example 2 and Examples 7 - 9, it was found that as the CoP content increased, the production rate of alanine increased, and the optimal mass ratio of CoP was approximately 5 wt%. However, when the CoP content reached 7.5 wt%, the production rate of alanine decreased, which might be due to the shielding effect of excessive CoP.

[0073] Comparative Example 1

[0074] Referring to the preparation process of cobalt phosphide / cadmium sulfide in Example 1, cobalt acetate hydrate was changed to ferrous nitrate nonahydrate, and finally a ferrous phosphide / cadmium sulfide catalyst with a mass ratio of ferrous phosphide to cadmium sulfide of 1:20 was obtained, and then the photocatalytic reaction was carried out.

[0075] Disperse 10 mg of the above - prepared ferrous phosphide / cadmium sulfide catalyst in 10 mL of ammonia water containing 100 mg of polylactic acid plastic to obtain a reaction solution, and add the reaction solution to a light - transmissive reactor. Then, purge the reactor with nitrogen for 30 minutes to remove dissolved oxygen. Under 1 bar of nitrogen, irradiate the reaction solution with a 300 - W xenon lamp, and at the same time control the reaction solution at 80 °C for reaction. After testing, within the initial 5 h, the production rate of alanine reached 1.35 mmol g cat -1 h -1 。

[0076] Comparative Example 2

[0077] Referring to the preparation process of cobalt phosphide / cadmium sulfide in Example 1, cobalt acetate hydrate was changed to nickel nitrate hexahydrate, and finally a nickel phosphide / cadmium sulfide catalyst with a mass ratio of nickel phosphide to cadmium sulfide of 1:20 was obtained, and then the photocatalytic reaction was carried out.

[0078] Disperse 10 mg of the above - prepared nickel phosphide / cadmium sulfide catalyst in 10 mL of ammonia water containing 100 mg of polylactic acid plastic to obtain a reaction solution, and add the reaction solution to a light - transmissive reactor. Then, purge the reactor with nitrogen for 30 minutes to remove dissolved oxygen. Under 1 bar of nitrogen, irradiate the reaction solution with a 300 - W xenon lamp, and at the same time control the reaction solution at 80 °C for reaction. After testing, within the initial 5 h, the production rate of alanine reached 2.07 mmol g cat -1 h -1 。

[0079] Comparative Example 3

[0080] Disperse 10 mg of cadmium sulfide prepared in Example 1 in 10 mL of ammonia water containing 100 mg of polylactic acid plastic to obtain a reaction solution, and add the reaction solution to a light-transmitting reactor. Then, purge the reactor with nitrogen for 30 minutes to remove dissolved oxygen. Under 1 bar of nitrogen, irradiate the reaction solution with a 300-W xenon lamp while controlling the reaction solution at 80 °C for reaction.

[0081] It was tested that within the initial 5 h, the production rate of alanine reached 0.56 mmol g cat -1 h -1 。

[0082] Based on the experimental results of Example 2 and Comparative Examples 1-3, it was found that when the cocatalysts (Fe2P, CoP, Ni2P) were loaded on CdS, the production rate of alanine was significantly increased compared with that before loading. Among them, CoP / CdS showed the highest activity, which was 2.4 mmol g cat -1 h -1 。

[0083] Example 10

[0084] Disperse 300 mg of cobalt phosphide / cadmium sulfide catalyst prepared in Example 1 in 20 mL of ammonia water containing 3 g of different waste polylactic acid plastics to obtain a reaction solution, and add the reaction solution to a light-transmitting reactor, where the waste polylactic acid plastics do not need to be crushed, just cut into small pieces. Then, purge the reactor with nitrogen for 30 minutes to remove dissolved oxygen. Under 1 bar of nitrogen, irradiate the reaction solution with a 300-W xenon lamp while controlling the reaction solution at 80 °C for reaction, and the test results are shown in Table 3.

[0085] Table 3

[0086] Waste polylactic acid plastic Reaction time Final alanine production Final alanine yield Waste PLA straw 72h 2.13g 56.6% Waste PLA cup 72h 1.93g 51.2% Waste PLA knife 72h 2.01g 53.3%

[0087] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, rather than limitations on the embodiments of the present invention. For those of ordinary skill in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to enumerate all the embodiments here. Any obvious changes or modifications derived from the technical solutions of the present invention still fall within the protection scope of the present invention.

Claims

1. A method for preparing alanine from photo-reformed polylactic acid plastic, characterized in that, It includes the following steps: Put polylactic acid plastic and a photocatalyst into ammonia water to obtain a reaction solution, and add the reaction solution into a light-transmitting reactor; Under an inert atmosphere, irradiate the reaction solution with a light source, and carry out a photocatalytic reaction by irradiating for 5 - 20 h at 60 - 80 °C to obtain alanine; Among them, the photocatalyst is selected from cobalt phosphide / cadmium sulfide.

2. The method according to claim 1, characterized in that, The mass ratio of the polylactic acid plastic to the photocatalyst is 5 - 20:

1.

3. The method according to claim 1, wherein The mass ratio of the cobalt phosphide to the cadmium sulfide is 1:13 - 33.

4. The method according to claim 1, wherein The photocatalyst is prepared according to the following steps: Dissolve cadmium salt and thiourea in ethylenediamine in sequence, stir for 20 - 30 min, then transfer it into a stainless-steel reaction kettle with a polytetrafluoroethylene inner liner, and heat at 150 - 160 °C for 24 - 48 hours to obtain cadmium sulfide nanorods; Add the cadmium sulfide nanorods into a mixed solution of ethanol and water, add cobalt salt and ammonia water thereto, heat at 70 - 90 °C for 20 - 25 hours, then transfer it into a stainless-steel reaction kettle with a polytetrafluoroethylene inner liner, and heat at 140 - 160 °C for 3 - 5 hours to obtain cobalt tetroxide / cadmium sulfide; Mix and grind the cobalt tetroxide / cadmium sulfide and sodium hypophosphite, transfer it to a tubular furnace, and calcine under an inert atmosphere to obtain cobalt phosphide / cadmium sulfide.

5. The method according to claim 4, wherein The cadmium salt is selected from cadmium nitrate tetrahydrate; The molar ratio of the cadmium salt to the thiourea is 1:2 - 3.

6. The method according to claim 4, wherein The cobalt salt is selected from cobalt acetate tetrahydrate and / or cobalt nitrate hexahydrate; The mass ratio of the cadmium sulfide nanorods to the cobalt salt is 5 - 7:

1.

7. The method according to claim 4, characterized in that The roasting conditions are heating at a rate of 2-3 °C·min -1 to 300-350 °C and holding for 3-5 h.

8. The method according to claim 1, wherein The light source is selected from one of sunlight, xenon lamp, mercury lamp, and LED lamp.

9. The method according to claim 1, characterized in that After the photocatalytic reaction is completed, it also includes separating and purifying the product.

10. The method according to claim 9, characterized in that, The steps of the separation and purification are: Centrifuge the reaction solution after irradiation and filter it through a polyethersulfone filter membrane, and after decolorization, rotary evaporation, and recrystallization, alanine crystals are obtained.

Citation Information

Patent Citations

  • Method for catalyzing thermal decomposition of polylactic acid

    CN115073416A

Cited By

  • Continuous cascade production method of alanine under photoelectric cooperative driving

    CN122102929A